Frontal interhemispheric structural connectivity, attention, and executive function in children with perinatal stroke. Issue 1 (25th November 2021) - Larsen, Nicole; Craig, Brandon T.; Hilderley, Alicia J.; Virani, Shane; Murias, Kara; Brooks, Brian L.; Kirton, Adam; Carlson, Helen L.
Abstract: Perinatal stroke affects ∼1 in 1000 births and concomitant cognitive impairments are common but poorly understood. Rates of Attention Deficit/Hyperactivity Disorder (ADHD) are increased 5–10× and executive dysfunction can be disabling. We used diffusion imaging to investigate whether stroke‐related differences in frontal white matter (WM) relate to cognitive impairments. Anterior forceps were isolated using tractography and sampled along the tract. Resulting metrics quantified frontal WM microstructure. Associations between WM metrics and parent ratings of ADHD symptoms (ADHD‐5 rating scale) and executive functioning (Behavior Rating Inventory of Executive Function (BRIEF)) were explored. Eighty‐three children were recruited (arterial ischemic stroke [AIS] n  = 26; periventricular venous infarction [PVI] n  = 26; controls n  = 31). WM metrics were altered for stroke groups compared to controls. Along‐tract analyses showed differences in WM metrics in areas approximating the lesion as well as more remote differences at midline and in the nonlesioned hemisphere. WM metrics correlated with parental ratings of ADHD and executive function such that higher diffusivity values were associated with poorer function. These findings suggest that underlying microstructure of frontal white matter quantified via tractography may provide a relevant biomarker associated with cognition and behavior in children with perinatal stroke. Abstract : Perinatal stroke affects ∼1 in 1000 births and concomitant cognitive impairments such as Attention Deficit/Hyperactivity Disorder (ADHD) and executive dysfunction can be disabling. We used diffusion tensor imaging (DTI) to investigate whether stroke‐related differences in frontal white matter (WM) relate to cognitive impairments. WM metrics correlated with parental ratings of ADHD and executive function suggesting that underlying microstructure of frontal white matter quantified via tractography may provide a relevant biomarker associated with cognition and behavior in children with perinatal stroke.